VDR Gene Polymorphisms in Healthy Individuals with Family History of Premature Coronary Artery Disease - Fronczek, Martyna; Strzelczyk, Joanna Katarzyna; Osadnik, Tadeusz; Biernacki, Krzysztof; Ostrowska, Zofia (Disease markers, 2021)
Aim. The gene encoding the vitamin D receptor (VDR) is considered in many studies to be a good candidate responsible for susceptibility to several diseases such as coronary artery disease (CAD). Epidemiological data show that cardiovascular disease is one of the major health problems in Polish society. Basic studies show that genetic factors play a significant role in the pathogenesis of CAD. We conducted this clinical study to determine if the VDR gene polymorphisms TaqI (rs731236), ApaI (rs7975232), and FokI (rs2228570) could predispose healthy individuals to an increased risk of premature CAD (P-CAD) incidents. Methods. We genotyped 845 subjects in a cohort consisting of 386 healthy volunteers with a documented P-CAD incident in their first-degree relatives and 459 healthy volunteers without family history (FH) of P-CAD. TaqI, ApaI, and FokI polymorphisms in VDR were genotyped using TaqMan assays and the endpoint genotyping method (qPCR). Statistical analyses were performed using the Power Analysis Software STATISTICA v.13.3. Results. Although no statistical significance was found for TaqI and ApaI genotype frequencies, the AA genotype of FokI polymorphism was significantly more frequent in the study group compared to the control group (24.61% vs. 16.99%). The results of logistic regression analysis suggested a significant association between FokI polymorphism and FH of P-CAD in heathy people under the recessive model (OR: 1.26 (1.07-1.49, p=0.007)); however, the frequency of VDR haplotypes did not differ significantly between the control and study populations. Conclusions. FokI polymorphism is may be associated with FH of P-CAD. FokI polymorphism may predispose to the development of P-CAD among healthy people over the next years.